Sulfoxonium Ylide Derived Metal Carbenoids in Organic Synthesis - Vaitla, Janakiram; Bayer, Annette (Synthesis, 2019)
As pioneered by Corey and Chaykovsky, sulfoxonium ylides have had widespread application in organic synthesis for more than a half century. In most of the reactions, sulfoxonium ylides were used to react with electrophiles. Under suitable reaction conditions these ylides can generate metal carbenoids and react with nucleophiles. By combining the typical reactivity of sulfoxonium ylides with transition-metal catalysis, a growing number of investigations have expanded their application in organic synthesis. This review provides an update on the preparation of sulfoxonium ylides and their applications in carbenoid transfer reactions.1 Introduction2 Preparation of Sulfoxonium Ylides3 Investigation for Carbenoid Formation from Sulfoxonium Ylide4 X–H (X = N, O, S, C) Functionalization Reactions5 Polymerizaton of Carbenoids Generated from Sulfoxonium Ylides6 Conclusion and Perspective
Keywords: sulfur ylides; metal carbenoids; transition metal catalysis; insertion reactions; C–H activation; coupling reaction; heterocycles